Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper analyzes the sectoral trends and the impact of the real effective exchange rate (REER) changes on sectoral exports using the detailed product data from the United Nations' Commodity Trade Statistics Database (Comtrade). This paper focuses on Uruguay's product- and sector-specific global export market shares. It also estimates the sensitivity of these market shares to real effective exchange rate by using the product data from the Comtrade database and building on the work presented in IMF (2017). The paper estimates the elasticities of product market shares with respect to real exchange rates for Uruguay only. Rather than using time dummies to isolate the potential impact of the time trend, the lagged value of the change in shares as an additional independent variable has been added. The paper concludes that Uruguay's manufacturing exports are sensitive to the changes in REER, and, accordingly, that productivity-enhancing measures to promote competitiveness would be beneficial.